Low power regulated power supply / Noridahanim Mohamed and Norhayati Mohd. Yasin - Mohamed, Noridahanim; Mohd. Yasin, Norhayati (1994)
The objective of this project is to develop a control technique to obtain a good regulated dc power supply from variable ac input voltage. The regulated power supply means that the voltage and frequency are maintained between the specific range. Conventional PI and PID controllers are available to give satisfactory results for a system which requires some controls. But these techniques require development of complete models representing dynamics of the process to be implemented. The simplicity and versatility features of a personal computer can be used in order to avoid these complexity and difficulty. This project describes the development of a control technique to provide a reliable constant voltage supply through the use of solid-state devices and a personal computer. Experimental works were carried out for the proposed technique.